2002
DOI: 10.1177/019874290202700408
|View full text |Cite
|
Sign up to set email alerts
|

Class-Wide Curricular Modification to Improve the Behavior of Students with Emotional or Behavioral Disorders

Abstract: We examined the effects of class-wide curricular modification on the engagement and challenging behaviors of students enrolled in a self-contained science class. Participants were six students between the ages of 13 and 14, all with labels of severe emotional disturbance in addition to a variety of other diagnoses. Class-wide curricular modifications consisted of providing opportunities for choice making and ensuring that activities were of high interest to students. Findings showed that the curricular modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…This review of the research found several limitations in the studies designed to promote self-determination skills to students with EBD. First, two studies that characterized themselves as targeting self-determination were not included because the dependent variable was not tied to changes in selfdetermination (Jolivette, Wehby, Canale, & Massey, 2001;Kern, Bambara, & Fogt, 2002). Second, the small number of EBD participants (n = 46, 17%) makes generalizabilty or analysis of individual or ecological factors that impact intervention success difficult.…”
Section: Limitationsmentioning
confidence: 99%
“…This review of the research found several limitations in the studies designed to promote self-determination skills to students with EBD. First, two studies that characterized themselves as targeting self-determination were not included because the dependent variable was not tied to changes in selfdetermination (Jolivette, Wehby, Canale, & Massey, 2001;Kern, Bambara, & Fogt, 2002). Second, the small number of EBD participants (n = 46, 17%) makes generalizabilty or analysis of individual or ecological factors that impact intervention success difficult.…”
Section: Limitationsmentioning
confidence: 99%
“…Caio et al, 2002;Kroeger and Nelson, 2006;Longano and Greer, 2006) A functional analysis of disruptive behaviour and the effects of task sequence choice on classroom compliance and engagement (e.g. Carr, 1977;Kern et al, 1994; The effects of staff training on independent selfhelp performance (e.g. Macduff et al, 2001;Sewell et al, 1998) Limited information in the studies on how to assess teaching stimuli (novel items) for children who learn labels quickly; also, how to continue to include meaningful stimuli while teaching the skill of question-asking An analysis of teaching conditions was important in order to programme for generalization Daily life events (e.g.…”
Section: Mock Exammentioning
confidence: 99%
“…For example, research-based academic practices included placing a greater emphasis on matching curriculum to students' instructional levels through the use of curriculum-based assessment and progress monitoring (Shapiro, 1996) to prevent student boredom or frustration-experiences that often lead to the exhibition of challenging behavior. Other interventions included modifying curriculum to promote desirable behavior by making it more it stimulating and relevant (Dunlap & Kern, 1996;Kern, Bambara, & Fogt, 2002); increasing students' academic engaged time and active responding through direct instruction procedures (Carnine, Granzin, & Becker, 1988); and training teachers to recognize that effective academic instruction and effective behavior management are reciprocally and inextricably related (Dunlap & Kern, 1996).…”
Section: Other Research-based Practicesmentioning
confidence: 99%